Metabolomic Evaluation of Chronic Periodontal Disease in Older Adults - Wellington F. Rodrigues; Camila B. Miguel; Ferdinando Agostinho; Gabriela V. da Silva; Javier E. Lazo-Chica; Sandra M. Naressi Scapin; Marcelo H. Napimoga; Carlos A. Trindade-da-Silva; José E. Krieger; Alexandre da Costa Pereira; Carlo J. Freire Oliveira; Siomar de Castro Soares; et al. (Mediators of Inflammation)
Periodontal disease is an infectious inflammatory disease related to the destruction of supporting tissues of the teeth, leading to a functional loss of the teeth. Inflammatory molecules present in the exudate are catalyzed and form different metabolites that can be identified and quantified. Thus, we evaluated the inflammatory exudate present in crevicular fluid to identify metabolic biological markers for diagnosing chronic periodontal disease in older adults. Research participants were selected from long-term institutions in Brazil. Participants were individuals aged 65 years or older, healthy, or with chronic periodontal disease. Gas chromatography/mass spectrometry was used to evaluate potential biomarkers in 120 crevicular fluid samples. We identified 969 metabolites in the individuals. Of these, 15 metabolites showed a variable importance with projection score>1 and were associated with periodontal disease. Further analysis showed that among the 15 metabolites, two (5-aminovaleric acid and serine, 3TMS derivative) were found at higher concentrations in the crevicular fluid, indicating their potential diagnostic power for periodontal disease in older adults. Our findings indicated that some metabolites are present at high concentrations in the crevicular fluid in older adults with periodontal disease and can be used as biomarkers of periodontal disease.